Time for change? Bringing SCPHN Practice Assessment Documentation into the digital era. (2nd December 2022) - Wilde, Matt
Abstract : This article examines the need for innovation in the form of Practice Assessment Documentation (PAD) in SCPHN education following developments in undergraduate nursing and midwifery programmes across the UK, alongside regional demand and poor historical practice. To successfully identify the evidence base for this development, a critical appraisal of several papers from the available literature was undertaken to examine aspects such as the value and contribution which technology generates in the enhancement of student learning, and the theoretical drivers from both an educational and professional perspective. The article concludes there is a necessity for this development in meeting the educational needs of students, while increasing the robustness of the assessment process for assessors. This paper aims to drive the development of a national SCPHN PAD in accordance with the new Nursing and Midwifery Council's Standards of Proficiency and plans to evaluate the effectiveness of the developed SCPHN PAD at the end of the upcoming academic year 2022/23.